Wetlands as energy-dissipating systems - Pokorný, Jan; Květ, Jan; Rejšková, Alžběta; Brom, Jakub (Journal of industrial microbiology and biotechnology, 2010)
Since wetlands are ecosystems that have an ample supply of water, they play an important role in the energy budgets of their respective landscapes due to their capacity to shift energy fluxes in favor of latent heat. Rates of evapotranspiration in wetlands are commonly as high as 6-15 mm day⁻¹, testifying to the large amount of energy that is dissipated through this process. Emergent or semi-emergent wetland macrophytes substantially influence the solar energy distribution due to their high capacity for transpiration. Wetland ecosystems in eutrophic habitats show a high primary production of biomass because of the highly efficient use of solar energy in photosynthesis. In wetlands associated with the slow decomposition of dead organic matter, such as oligotrophic marshes or fens and bogs, the accumulation of biomass is also high, in spite of the rather low primary production of biomass. Most of the energy exchange in water-saturated wetlands is, however, linked with heat balance, whereby the largest proportion of the incoming energy is dissipated during the process of evapotranspiration. An example is shown of energy fluxes during the course of a day in the wetland ecosystem of Mokré Louky (Wet Meadows) near Třeboň. The negative consequences of the loss of wetlands for the local and regional climate are discussed.
Keywords: ekologie; rostliny; Plants; Fresh Water; Temperature; sluneční záření; Ecology; Wetlands; Photosynthesis; mokřady; transpirace rostlin; biomasa; sladká voda; teplota; Sunlight; Biomass; Plant Transpiration; fotosyntéza